Transformação em Produto

Lembretes dicas e truques para alunos e professores.




Transformação em produto


 

·        sen p + sen q = 2 . sen ( p+q / 2) . cos ( p – q /2)

·        sen p – sen q = 2 . sen ( p - q / 2) . cos ( p + q /2)

·        cos p + cos q = 2 . cos ( p+q / 2) . cos ( p – q /2)

·        cos p - cos q = -2 . sen ( p+q / 2) . sen ( p – q /2)

·        tg p + tg q = sen (p +q)/(cos p . cos q)

·        tg p - tg q = sen (p -q)/(cos p . cos q)

 

Exemplo:

 

1)      Fatore: y = sen 3x + sen x

Resolução

Fazemos (3x + x)/2 = 2x e (3x – x)/2 = x.

Daí:

y = 2. sen 2x . cos x = 2 . 2 sem x . cos x . cos x

y = 4 sen x . cos2 x

 

Resposta: y = 4 sen x . cos2 x

 

2)      Fatore: y = cos 3x + cos x

Resolução

Fazemos (3x + x)/2 = 2x e (x – 3x)/2 = -x.

Daí:

y = 2 . cos 2x . cos (-x) = 2 cos 2x cos x

 

Resposta: y = 2 cos 2x cos x